PENGARUH MINAT USAHA, KREATIVITAS, INOVASI, MOTIVASI, MODAL USAHA TERHADAP KEBERHASILAN USAHA WIRAUSAHA MUDA DI KECAMATAN BANGKALAN: indonesia - HOLILURROHMAN; Ika Lis Mariatun; Yusrianto Sholeh (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Entrepreneurship is one of the main aspects in the economic development and progress of a country. Where more and more people are entrepreneurs, the people who are entrepreneurs have reduced unemployment in a country. This is of particular concern to the Bangkalan government to increase MSMEs in the Bangkalan sub-district. This study aims to analyze the effect of business interest, creativity, innovation, motivation, and business capital on the success of young entrepreneurs in the Bangkalan sub-district. In this study using quantitative research. The population in this study is business people in the town square of Bangkalan sub-district. By using a saturated sampling technique that is as many as 30 traders. Data collection techniques used are questionnaires and documentation. The results of this study indicate that the results of the t test indicate that the t test results indicate that the interest in education variable (X1) obtains a tcount value of 1.292 > ttable 2.064 with a significance value of .209, the Creativity variable (X2) obtains a tcount value of 1.652> ttable 2.064 with a significance value of .112, the innovation variable (X3) obtained a tcount value of 2.389 > ttable 2.064 with a significance value of .025 , the variable Motivation (X4) obtained a tcount value of -1.592 > ttable 2.064 with a significance value of .125 , variable working capital (X5) obtained a tcount of 2.285 > ttable of 2.064 with a significance value of .031 partially the variables of business interest, creativity, innovation and venture capital affect business success (Y) while the motivational variable does not partially affect business success. The F test obtained Fcount 17.298 > Ftable 2.62 which indicates that all X variables simultaneously influence business success (Y).